Avaliação da remoção do ácido 2,4-diclorofenoxiacético (2,4-D) em águas através do uso de carvão granular (CAG) em pequenas colunas (escala experimental) - Rozário, Andréia do (2012)
The increased use of pesticides in Brazil has caused many concerns due to environmental and health problems they can cause. Many of these products are not efficiently removed by conventional treatment of water, requiring alternatives that remove the water supply. One option is the use of granular activated carbon (GAC) in fixed beds, because due to the high efficiency removal of microcontaminants and ease of operation, this technology is one of the most effective and reliable water treatment. The aim of this study was to evaluate, through the Rapid Tests in Small Scale Column (RSSCT), the adsorption capacity of GAC in removing 2,4-D in samples of distilled / deionized (DDW) and filtered from the water treatment plant (FWTP) fortified (only with 2,4-D or associated with atrazina or 2,4,5-T). Pesticides were detected and quantified using high performance liquid chromatography (HPLC), the methodology adapted and properly validated. Eight tests were performed with fixed beds in series, which varied the type of water used and the rate of surface application. The adsorption capacities obtained from water samples spiked with only 2.4-D had higher values than those obtained from isotherms. Furthermore, natural organic matter (NOM) had a great influence on the adsorption of 2,4-D, decreasing its adsorption capacity. In the tests performed with effluent spiked with only FWTP with 2,4-D was observed by absorbance values at 254 nm, the removal of the MON by CAG. Furthermore, there was a preferential adsorption of hydrophobic pesticides (2,4,5-T, and atrazine) to the 2,4-D, since in all tests water samples spiked with 2,4-D associated with 2,4,5-T or atrazine, there was a decrease in the adsorption capacity of the CAG.